Musculoskeletal symptoms in adolescents with internet gaming disorders - Şenel, Aybike; Atılgan, Elçin; Turhan, Merve; Özsoy, Rümeysa; Duman, Sümeyra; Ocak, Merve Nur; Özgün, Gülistan; Kölük, Hatice Kübra; Sünmez, Naime Simla; Mutlu, Caner; Kaya Mutlu, Ebru (Journal of Dependence, 2021)
Objective: The aim of this study was to examine the musculoskeletal symptoms in adolescents with internet gaming disorder (IGD). Method: A total of 80 participants were included to this prospective cross-sectional study. Participants were divided into two equal groups: healthy adolescents and adolescents diagnosed with IGD. After sociodemographic data were recorded, musculoskeletal symptoms of the participants were evaluated with a 26-question form which was prepared by the researchers. The severity of addiction of the participants was evaluated with Internet Addiction Scale. Results: The mean age was found 14,50 ± 2,10 in Group I, and 14,90 ± 1,72 in Group II with no significant difference between. The participants who agreed to the items “I do not pay attention to my pain while I am playing games” and “I feel my posture getting worse while I am playing games” were found statistically significant higher in Group II than in Group I. No significant difference was found between healthy adolescents and adolescents with IGD in terms of musculoskeletal symptoms. Conclusion: It can be intrepreted that adolescents with IGD could not report realistically of their symptoms that they already do not pay attention while they are playing games.